Teaching Vocabulary in a Digital Era: A Study on Tools and Techniques for Engaging English Learners - Haque, Arina; Ariansyah, Muchammad Ravli; Wiladyah, Nuro Choiril; Sari, Rista Novita (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2024)
Vocabulary acquisition is a cornerstone of language learning, essential for comprehension, communication, and overall proficiency. This critical review explores the evolving landscape of vocabulary instruction in the digital era, emphasizing the integration of innovative tools and techniques to enhance engagement and retention among English learners. It examines the transition from traditional, teacher-centered approaches to dynamic, learner-focused strategies enabled by technology. Digital tools, such as gamified platforms, multimedia resources, and mobile-assisted language learning applications, are highlighted for their ability to cater to various learning styles, promote learning autonomy, and sustain motivation. The review also discusses the role of contextual and personalized learning in improving vocabulary acquisition, drawing attention to strategies like spaced repetition, collaborative tools, and the use of media for immersive experiences. Additionally, it underscores the importance of balancing modern technology with foundational teaching methods to maximize effectiveness. The findings advocate for a strategic integration of traditional and digital methodologies, providing actionable insights for educators aiming to foster meaningful vocabulary development in diverse educational settings.